2020
DOI: 10.1002/pssb.201900705
|View full text |Cite
|
Sign up to set email alerts
|

Strain Recovery and Defect Characterization in Mg‐Implanted Homoepitaxial GaN on High‐Quality GaN Substrates

Abstract: The evolution of defects due to high‐pressure annealing of magnesium ion‐implanted epitaxial GaN grown on high‐quality GaN substrates is investigated. Changes in the implant‐induced strain are quantified as a function of annealing temperature and time. After annealing at 1300 °C for 10 min, the implant‐induced strain is fully relieved and accompanied by the presence of extended defects such as basal plane stacking faults and prismatic loops. Approximately one‐third of the original implant‐induced strain remain… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 14 publications
(7 citation statements)
references
References 43 publications
2
5
0
Order By: Relevance
“…However, the broader shoulders observed below the half maximum intensity of the sample annealed at 800 °C show that other extended defects may evolve during the annealing. This behavior has been observed in implanted and annealed GaN …”
Section: Resultssupporting
confidence: 61%
See 1 more Smart Citation
“…However, the broader shoulders observed below the half maximum intensity of the sample annealed at 800 °C show that other extended defects may evolve during the annealing. This behavior has been observed in implanted and annealed GaN …”
Section: Resultssupporting
confidence: 61%
“…This behavior has been observed in implanted and annealed GaN. 32 Figure 6c shows the comparison of calculated and measured thermal conductivity. The four samples studied in this work were heated to 450 °C during the exfoliation transfer process.…”
Section: ■ Introductionsupporting
confidence: 56%
“…[10,11] UHPA permits the use of high temperatures and long annealing durations without surface degradation. Using this technique, the implantation-induced strain is effectively removed, [12] and high acceptor activation percentages greater than 80% respective to implanted magnesium (Mg) ions have been obtained. [10,13,14] Unfortunately, prolonged annealing at high temperatures can promote the diffusion of Mg atoms so that the dopant dispersion profile is changed.…”
Section: Introductionmentioning
confidence: 99%
“…Early work by Servidori 8 for ion implanted silicon substrates showed that this distortion can be studied with X-ray diffraction (XRD) and a strain profile caused by the ion implantation can be extracted. Previous works have examined a wide roster of materials including Si 9 , III–V 10 , 11 , and II–VI 12 materials and employ both XRD measurements and Monte Carlo simulations to obtain strain and displacements-per-atom profiles of implanted materials. Out-of-plane lattice expansion due to the implantation is universally observed for previously studied materials.…”
Section: Introductionmentioning
confidence: 99%